Clarithromycin inhibits myometrial contractions in isolated human myometrium independent of stimulus - Celik, H; Ayar, A (Acad Sciences Czech Republic, Inst Physiology, 2002)
Erythromycin has a well-known dual effect on the contractility of the gastrointestinal system and recently has also been shown to inhibit contractions of the rat myometrium. The aim of the present study was to investigate the effects of clarithromycin on oxytocin, prostaglandin F-2alpha (PGF(2alpha)) and KCl-induced contractions of human myometrium in vitro. Myometrial strips were obtained from pregnant women undergoing elective Cesarean section and the strips were suspended in a jacketed organ bath filled with Krebs solution at 37 degreesC (pH 7.4) and continuously aired with 95 % oxygen and 5 % carbon dioxide. Isometric contractions were measured using a force displacement transducer. Oxytocin, PGF(2alpha), KCl and clarithromycin were applied to the tissue bath and the amplitude and frequency of contractions were evaluated at 20-min intervals. Freidmann analysis of variance, Kruskal Wallis and Wilcoxon Rank tests were used for statistical analysis of the data. Clarithromycin dose dependently inhibited the amplitude of contractions independent of the stimulus. Pre-treatment with apamin prevented clarithromycin-induced effects on amplitude and frequency of contractions. We conclude that the macrolide antibiotic clarithromycin may have a direct inhibitory effect on contractions of human myometrium.
Keywords: myometrium; clarithromycin; oxytocin; isometric contraction; human